Activity of pectinmethylesterase, pectin content and vitamin C in acerola fruit at various stages of fruit development - de Assis, S. A.; Lima, D. C.; Oliveira, OMMD (Elsevier B.V., 2001)
In order to know which stage of fruit development is better for acerola industrialization, we studied the PME specific activity, pectin content and vitamin C at various stages of development. The acerola fruits were classified according to colour and weight in five stages: immature green (2.62-3.21 g), green (4.04-4.83 g), mature green/yellow (5.03-5.88 g), pale-red (6.16-6.77 g) and ripe mature (6.92-8.37 g). The results showed that the highest content of pectin and vitamin C occurred at the immature green stage, 4.51 +/- 0.1% yield, 2424 mg/100 g of pulp and decreased as fruit ripened, 2.99 +/- 0.03% yield, 957 +/- 0.0 mg/100 g of pulp, respectively. However, at the same stages, the values of PME specific activity were lowest, 0.61 +/- 0.01 and 0.55 +/- 0.0 units g(-1)/g of pulp, respectively. The highest value of PME activity was 2.08 +/- 0.01 units g(-1)/g of pulp in the green stage. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: pectin methylesterase; pectin; vitamin C; acerola; fruit development